2016
DOI: 10.1007/s10854-016-5042-z
|View full text |Cite
|
Sign up to set email alerts
|

A new route to fabricate PbS nanofibers and PbSe nanofibers via electrospinning combined with double-crucible technique

Abstract: PbO nanofibers were fabricated by calcination of the electrospun PVP/Pb (NO 3 ) 2 composite nanofibers. For the first time, PbS nanofibers and PbSe nanofibers were successfully synthesized by double-crucible sulfurization and selenidation methods using PbO nanofibers as precursors, respectively. X-ray diffraction (XRD) analysis shows PbS nanofibers and PbSe nanofibers are respectively pure cubic phase with space group of Fm-3 m. Scanning electron microscope (SEM) observation indicates that the diameter of PbS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Semiconductor based photocatalysis has attracted considerable attentions owing to its promising application in solar energy conversion and environmental purification [1][2][3][4][5][6] . Perovskite oxide has been proven to be an important class of photocatalysts 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor based photocatalysis has attracted considerable attentions owing to its promising application in solar energy conversion and environmental purification [1][2][3][4][5][6] . Perovskite oxide has been proven to be an important class of photocatalysts 7 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated the crucial role that this compound's distinctive structural and electronic characteristics play. [21][22][23][24][25][26] Notably, the perovskite structure exhibits a remarkable degree of symmetry, which contributes significantly to its photovoltaic applications. Furthermore, the defect-tolerant nature of CH 3 NH 3 PbI 3 further enhances its photovoltaic performance.…”
mentioning
confidence: 99%
“…The intensity of these characteristic peaks also depends on the PE kinetic energy used. With 30-keV PEs, prominent peaks near 1.74 keV, 2.35 keV, 3.44 keV, and 3.94 keV were attributed to X-ray emission from silicon (K α band), lead (M α band), tin (L α band) and iodine (L α1 band) [54][55][56][57] . The lead and iodine signals originated from the FAPbI 3 layer, while the tin and silicon only existed in the substrate, signaling a deep penetration of the 30-keV PEs.…”
Section: Probing Ion Distribution Within Different Depthsmentioning
confidence: 99%